A unicorn in Alice in Wonderland syndrome - Landais, Anne (World J Nucl Med, 2019)
We report the case of a 56-year-old man presenting several episodes of body image distortions with a sensation of having a horn growing on his forehead, as a unicorn, corresponding to the Alice in Wonderland syndrome. Brain single-photon emission computed tomography with technetium-99m hexamethylpropyleneamine oxime showed hypoperfusion of the visual primary cortex, expanding to the temporo-occipital junction bilaterally but predominantly on the right side.